Related Factors With The Implementation Of Tetanus Diphtheria Immunization in Pregnant Women - Diah Triratnasari (Universitas Airlangga, 2017)
Tetanus problems are still the cause of neonatal death in Indonesia. Maternal and Neonatal Tetanus Elimination Program is a program to improve maternal and child health and evenly to be free from Tetanus disease by Immunization of Tetanus Diphtheria during pregnancy, its aims to build immunity in the mother and baby to avoid Tetanus infection. Tetanus Neonatorum case in 2014 in Indonesia amounted to 54 cases with the non-immunization status of Tetanus Diphtheria. The number of pregnant women targeted by Tetanus Diphtheria immunization in the work area of Burneh Sub-District Health Center of Bangkalan District is 1073 pregnant women in 2016, but it just covered 585 pregnant women. This research was conducted with a cross sectional design with the number of samples taken by 93 mothers who became the target of Tetanus Diphtheria Immunization and had given birth in 2016 by using simple random sampling. The purpose of this study was to analyze factors related to the participation of pregnant women in the implementation of Tetanus Diphtheria immunization in the work area of Burneh Sub-District Health Center 2016. The results of this study indicate that the age of the respondents is mostly aged 20 years to 30 years, with the number of children owned by respondents mostly amounted to 1. Lower knowledge possessed by respondents about tetanus disease and Tetanus Diphtheria immunization, so that health workers and family roles have an important role to encourage respondents to have awareness to immunize Tetanus Diphtheria during pregnancy. Keywords: husband support, Tetanus Diphtheria Immunization, knowledge, officer attitude